2021
DOI: 10.18186/thermal.849869
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Parabolic Trough Collector With Receiver Position Error

Abstract: In the present study, the effect of receiver position error on the optical and thermal performance of a parabolic trough collector (PTC) has been studied. Optical analysis of the PTC has been carried out by using Monte Carlo ray tracing (MCRT) method. The solar heat flux profile obtained from the optical analysis is coupled with the finite volume method (FVM) to study the thermal performance of the PTC. Simulations have been done for experimental SEGS LS2 solar collector used in Sandia National Laboratories. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…It is important to design by figuring out what these errors are and what they mean for how well PTC works. Donga et al [5] studied the influence of receiver location on the optical and thermal performance of a PTC. The simulation was carried out by coupling MCRT heat flux distribution data with CFD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to design by figuring out what these errors are and what they mean for how well PTC works. Donga et al [5] studied the influence of receiver location on the optical and thermal performance of a PTC. The simulation was carried out by coupling MCRT heat flux distribution data with CFD.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the numerical results were quite close to the experimental results. Among other techniques, the MCRT method is extensively used for obtaining focused solar heat flux distribution [5,6,9,11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Donga et al investigated the impact of receiver position error on thermal and optical efficiency in PTC systems. Researchers found that the collector thermal efficiency drops by 14% for the position error of 1.63% from the focal point [12]. Afsharpanah et al numerically investigated the impact of using different types of twisted tapes in PTC systems for performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the displacement of 1.6% of the receiver from the collector's focal length the receiver resulted in a loss of 32% in PTC efficiency. 23 Recently, the thermal modeling of PTC with different tools was investigated. Detailed thermal modeling of a PTC using the engineering equation solver (EES) and considering the modes of heat transfer was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The method of Monte Carlo ray tracing was implemented to study the effect of the error of receiver position on the PTC performance. The authors found that the displacement of 1.6% of the receiver from the collector's focal length the receiver resulted in a loss of 32% in PTC efficiency 23 …”
Section: Introductionmentioning
confidence: 99%